Creating sustainable learning environments for a grade 10 accounting classroom: a critical accounting approach - Qhosola, Makeresemese Rosy (University of the Free State, 2016)
The way in which accounting is taught in the Grade 10 classroom, presents a challenge to the pedagogical content knowledge. More teacher – centred methods of teaching are widely used, where memorisation with the focus on the examination is common. The textbook is still the primary source of instruction. Content is mainly abstract to which learners struggle to relate, in a way which is meaningful to their lives. The teaching of accounting contradicts with the key documents that are constitutionally derived. The roles of teachers are compromised intensively, in a way that undermines facilitative strategies and the ability to use suitable assessment strategies, which result in unsustainable learning environments. On the basis of the above, the study aims to formulate a strategy to create a Sustainable Learning Environment for a Grade 10 accounting class using a Critical Accounting Approach. In order to achieve this, the following specific objectives were derived to guide the study: - To analyse and understand the challenges in the creation of SuLE for a Grade 10 accounting classroom - To explore strategies in the creation of SuLE using the Principles of Critical accounting approach - To investigate the conditions that make the creation of SuLE through the use of Principles of Critical accounting approach - To anticipate possible threats to that might hamper the creation of SuLE through the use of Principles of Critical accounting approach - To identify the indicators of success and lack thereof. Critical accounting research (CAR) is used as the theoretical framework informing the study. It contains assumptions that guide and direct the thinking and actions taken by the researcher and participants. It is the best-suited theoretical framework for the study because of its recognition that accounting is a social science and not a mere collection of abstract mathematical manipulations or calculative routines. CAR is the lens positioning my stance in relation to the participants in an aspect of the whole study. The critical accounting framework is used for the study since it can offer many opportunities for students to explore and transform their knowledge in a way meaningful not only to them but also to the benefit of society. Furthermore CAR complements the research design and methodology of the study which is the Participatory Action Research (PAR) approach because they are both concerned about the impact of accounting to the community and society at large. PAR is a philosophical approach to research that recognises the need for persons being studied to participate in the design and conduct of all phases of any research that involves them. It is through PAR that the meetings, dialogues, discussions with the focused groups were conducted, which consisted of lecturers, students, subject heads, coordinators and members of NGO’s as well as departmental officials, the results were analysed through Critical discourse analysis since it allowed for the use of text by participants. The study revealed its findings and recommendations as well as conditions that would make the recommendations work, while indicating possible threats and ways to circumvent them and indicators of the successful implementation of the strategy are discussed. Many findings led to the conclusion that the teaching of accounting should be optimal as a result of effective teaching and learning strategies which are learner-centred, promote self-regulated learning, and are compatible with the prescripts of a democratic constitution of the country such as equity, social justice, peace, freedom and hope. The study ends by proposing a strategy to create a Sustainable Learning Environments for a Grade 10 accounting using a Critical Accounting Approach, which include the same components as used in the study itself.

Die manier waarop rekeningkunde in die Graad 10-klaskamer onderrig word, bied ‘n uitdaging vir die pedagogiese inhoudkennis. Onderwyser-gesentreerde benaderings tot onderrig word algemeen gebruik soos memorisering van feite met die oog op eksaminering. Die handboek bly die primêre bron van onderrig. Leerders sukkel om sin te maak van die abstrakte aard van die onderrigmateriaal sodat dit sinvol is in hul lewens. Die onderrig van Rekeningkunde is teenstrydig met die belangrike dokumente. Die rol van die onderwysers word gekompromitteer op ‘n manier wat fasiliteringsstrategieë en die gebruik van geskikte assesseringsstrategieë ondermyn en lei tot ‘n onVolhoubare leeromgewing. Op grond van bogenoemde beoog hierdie studie om ‘n strategie te formuleer wat ‘n Volhoubare Leeromgewing (VLo) te skep vir ‘n graad 10 rekeningkunde klas waar ‘n Kritiese rekeningkunde benadering gevolg word. Om hierdie ideaal te verwesenlik, sal die volgende doelstellings as wegwysers vir die studie dien: - Om die uitdagings by die skep van ‘n VLo vir ‘n Graad 10 Rekeningkunde klas te analiseer en verstaan - Om strategieë vir die skep van ‘n VLo deur die beginsels van ‘n Critical Accounting benadering te verken - Om die toestande wat die skep van ‘n VLo deur die aanwending van die beginsels Critical Accounting moontlik maak te ondersoek - Om moontlike bedreigings tot die skep van ‘n VLo deur die gebruik van die beginsels van Critical Accounting te antisipeer - Om die aanwysers van sukses of die gebrek daaraan vas te stel Kritiese Rekeningkunde Navorsing (CAR) word as teoretiese raamwerk in hierdie studie aangewend en dit onderskraag die aannames wat die denke en optrede van die navorser en deelnemers aan die studie beïnvloed. Hierdie is die mees gepaste teoretiese raamwerk omdat dit rekeningkunde as sosiale wetenskap erken eerder as bloot ‘n versameling abstrakte wiskundige manipulasies of berekeningroetines nie. CAR is die lens wat my posisionering ten opsigte van die deelnemers aan hierdie studie bepaal. Hierdie kritiese rekeningkunde raamwerk word aangewend omdat dit studente veelvoudige geleenthede bied om hulle kennis te verken en aan te pas op ‘n betekenisvolle wyse om nie net hulself nie, maar ook die gemeenskap te bevoordeel. Boonop komplimenteer CAR die navorsingsontwerp en metodologie van hierdie Aksienavorsing projek aangesien beide besorgd is oor die inwerking van rekeningkunde op die gemeenskap, in die kleine en die breë gemeenskap. Aksienavorsing is ‘n filosofiese benadering tot navorsing wat die behoefte van deelnemers aan navorsing om deel te neem aan die ontwerp van, en die uitvoer van alle dele van die navorsingsprojek waar hulle respondente is. Dit is deur aksienavorsing dat die vergaderings, samesprekings en besprekings met die fokusgroepe gehou is. Fokusgroepe is saamgestel uit groepe dosente, studente, vakhoofde, koordineerders, lede van NGO’s sowel as departementele beamptes. Die data analise is gedoen deur middel van Kritiese Diskoersanalise aangesien hierdie metode toelaat dat respondente teks kan gebruik. Daar is bevindinge en aanbevelings sowel as toestande wat die uitvoer van die aanbevelings bevorder. Moontlike bedreigings vir die uitvoer van die aanbevelings word uitgewys met voorstelle hoe die bedreigings omseil kan word en dan word aanduiders van die suksesvolle implimentering van die strategie ook bespreek. Die bevindinge van die navorsing wys dat die onderrig van Rekeningkunde gunstig behoort te wees as gevolg van effektiewe leer- en onderrigstrategieë wat leerdergesentreerd is en selfregulerende studie bevorder. Hierdie strategieë moet saamval met die bepalings van ‘n demokratiese grondwet wat onder meer gelykheid, vrede, vryheid en hoop insluit. Die studie sluit af met ‘n voorstel vir ‘n strategie wat die Critical Accounting Approach gebruik om ‘n Volhoubare Leeromgewing vir Graad 10 Rekeningkunde te skep met dieselfde komponente wat in hierdie navorsing gebruik is
Thesis (Ph.D. (School of Education Studies))--University of the Free State, 2016
Keywords: Grade 10; Classroom; Sustainable learning environment; Critical accounting research; Critical discourse analysis; Participatory action research